2017
DOI: 10.1002/2017gb005708
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Climate Controls on North Atlantic Marine Carbon Dynamics Over the Last Millennium: Insights From an Absolutely Dated Shell‐Based Record From the North Icelandic Shelf

Abstract: Given the rapid increase in atmospheric carbon dioxide concentrations (pCO2) over the industrial era, there is a pressing need to construct long‐term records of natural carbon cycling prior to this perturbation and to develop a more robust understanding of the role the oceans play in the sequestration of atmospheric carbon. Here we reconstruct the past biological and climate controls on the carbon isotopic (δ13Cshell) composition of the North Icelandic shelf waters over the last millennium, derived from the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 70 publications
(155 reference statements)
1
19
0
Order By: Relevance
“…Analysis of the GoM_C isotopic measurements support the hypotheses that A. islandica shells growing in the same environment record consistent oxygen isotopic information in their carbonate structures (e.g., Mette et al, 2016) and that, between individuals, carbon isotope values are more variable at young ages (Butler et al, 2011;Reynolds et al, 2017). The range of temperatures derived from the  18 O values (13.52 to 15.97 °C) is larger than the range of temperatures in which the shells were grown (14.95 ±0.06 °C, last nine days).…”
Section: Culture Experimentsmentioning
confidence: 55%
See 2 more Smart Citations
“…Analysis of the GoM_C isotopic measurements support the hypotheses that A. islandica shells growing in the same environment record consistent oxygen isotopic information in their carbonate structures (e.g., Mette et al, 2016) and that, between individuals, carbon isotope values are more variable at young ages (Butler et al, 2011;Reynolds et al, 2017). The range of temperatures derived from the  18 O values (13.52 to 15.97 °C) is larger than the range of temperatures in which the shells were grown (14.95 ±0.06 °C, last nine days).…”
Section: Culture Experimentsmentioning
confidence: 55%
“…Inter-shell  13 C variability for the GoM_C shells measured 0.65 ‰ (2, mean between splits; Table 2), compared to 2 analytical uncertainty of 0.17 ‰ for  13 C. The unexpected and relatively large variability in  13 C values between individuals, in this case, is hypothesized to arise from vital effects during early ontogeny (for example, see Butler et al, 2011 andReynolds et al, 2017). Beirne et al (2012) found that both juvenile and adult A. islandica clams incorporated ~10% of metabolic carbon into their shells, however, a positive relationship between juvenile (2-3 year old) growth rates and  13 C values was found during the spring bloom period (March-May; r 2 = 0.23; p < 0.012).…”
Section: Culture Experimentsmentioning
confidence: 92%
See 1 more Smart Citation
“…Based on these considerations, we chose to not correct the planktic δ 13 C record for the Marine Suess effect as done elsewhere [e.g. 75].…”
Section: Foraminifera Trace Anthropogenic Co 2 In the Iceland Sea By~mentioning
confidence: 99%
“…For example, regionally crossdated bivalve series demonstrate highly synchronous Ba/Ca ratios in shell aragonite potentially related to productivity dynamics [39]. Stable carbon ( 13 C) isotope values [40] from exactly dated increments provide constraints on carbon cycling and the socalled Suess effect [41,42] through space and time. Moreover, radiocarbon measurements from exactly dated increments can be used to assess changes in circulation and provide tight constraints for the marine reservoir effect [10,25,37].…”
Section: Pastmentioning
confidence: 99%